1978
DOI: 10.2466/pms.1978.46.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Motor Development and Self-Concept: Race and Age Differences

Abstract: To investigate the effect of organized physical activity on the development of specific motor skills (body coordination and self-concept) of elementary age children, 344 children from the ethnic origins, black and white, were administered the Schilling Body Coordination Test and the Martinek-Zaichkowsky Self-concept Scale for Children. Motor development (body coordination) and self-concept scores were significantly higher for the group who participated in the physical activity program than for controls who did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…In a study to determine the effect of a running program on self-concept of college students, Hilyer and Mitchell (1979) revealed that college students with low self-concept increased both their fitness levels and their self-concept scores. Other studies have shown similar positive results (Martinek, Cheffers, & Zaichkowsky, 1978;Wright & Cowden, 1986). These and other studies suggest that proficiency in physical activities could enhance self-concept.…”
supporting
confidence: 63%
“…In a study to determine the effect of a running program on self-concept of college students, Hilyer and Mitchell (1979) revealed that college students with low self-concept increased both their fitness levels and their self-concept scores. Other studies have shown similar positive results (Martinek, Cheffers, & Zaichkowsky, 1978;Wright & Cowden, 1986). These and other studies suggest that proficiency in physical activities could enhance self-concept.…”
supporting
confidence: 63%
“…Finally, a third series of studies have reported positive psychological changes accompanying physical exercise in specialized populations such as children (15), collge students (16), cardiac patients (17), or psychiatric patients (18,19).…”
mentioning
confidence: 96%
“…In order to gather meaningful data from especially the younger children, it was necessary to develop nonverbal instruments Downloaded by [Nanyang Technological University] at 01:29 06 June 2016 and to validate new instruments with more specific intent. Instruments measuring attitudes, preferences, self-concept, involvement, interaction, creativity, motorskill development, and fitness were used during these energetic years Martinek, Zaichkowsky, & Cheffers, 1977;Cheffers & Evaul, 1978;Martinek, Zaichkowsky, & Cheffers, 1978;: Schempp, Cheffers, & Zaichkowsky, 1983Lydon & Cheffers, 1984;Lydon & Cheffers, 1984;Cheffers & Crowley-Sullivan, 1990;Cheffers, 1992;Nastasi & Cheffers, 1992;Cheffers, 1993;Kelly, 1996;Lydon & Cheffers, 1984). No instrument was used that was not vaIid or reliable.…”
Section: Researchmentioning
confidence: 99%
“…Martinek et al (1978) investigated the effect of physical activity on motor-skill development (body coordination) and self-concept with 344 children from ethnic origins, Black, and White. They used the Schilling Body Coordination tests and the Martinek Zaichkowsky Self-concept Scale for Children.…”
Section: Researchmentioning
confidence: 99%